Odpowiedź :
A= <-10;-2> , B= (-∞; 0), C= <-4; 5)
a.)
C u A = <-10; 5)
B \ (C u A) = (-∞; -10)
b.)
B n C = <-4; 0)
(B n C) \ A = (-2; 0)
c.)
C \ B = <0; 5)
R \ (C\ B) = (-∞; 0) u <5; +∞)
a.)
C u A = <-10; 5)
B \ (C u A) = (-∞; -10)
b.)
B n C = <-4; 0)
(B n C) \ A = (-2; 0)
c.)
C \ B = <0; 5)
R \ (C\ B) = (-∞; 0) u <5; +∞)
a) =(- nieskonczonosc;-10)
b) =(- nieskonczonosc;-10)U(-2;5)
c)=(- nieskonczonosc;0)U(5;+nieskończoność)
b) =(- nieskonczonosc;-10)U(-2;5)
c)=(- nieskonczonosc;0)U(5;+nieskończoność)
a.) B\ (С υ A)
(С υ A) = <-10;5)
B\ (С υ A) = (-∞;-10)
b.) (B П C) \ A
(B П C) = <-4;0)
(B П C) \ A = zbiór pusty
c.) R \ (C\ B)
(C\ B) = <0;5)
R \ (C\ B) = (-∞;0) υ <5;∞)
(С υ A) = <-10;5)
B\ (С υ A) = (-∞;-10)
b.) (B П C) \ A
(B П C) = <-4;0)
(B П C) \ A = zbiór pusty
c.) R \ (C\ B)
(C\ B) = <0;5)
R \ (C\ B) = (-∞;0) υ <5;∞)